Issues Regarding Adolescents Sexual and Reproductive Health in Sarawak : An Overview - Gerraint Gillan, Ahi; Md Mizanur, Rahman (UNIMAS Publisher, 2023)
Adolescents’ sexual and reproductive health is a commonly discussed topic in public health research. In Sarawak, similar challenges have been faced in other parts of the world which are, lack of access to accurate and comprehensive information about safe sex, contraception access and usage, and sexually transmitted infections (STIs) whereby the adolescents will commit a risky sexual activity that affects their physical, mental and their socio-economic status. The Ministry of Women, Early Childhood and Community Wellbeing Development has stated that the cases of teenage pregnancy are rising in recent years as adolescents are engaging in risky sexual behaviour. Such cases occur due to adolescents experiencing sexual novelty during their growth and development period. Misconception about sex also contributes to risky sexual activity among adolescents as the source of information about sex they obtain is from media and pornography. Efforts have been made to enhance the knowledge of sexual and reproductive health among adolescents in Sarawak including school-based sex education and community outreach initiatives. However, there are still many efforts to be achieved to ensure that adolescents have access to the information and resources they need to make informed decisions about their sexual and reproductive health.